Avaliação do sistema purinérgico em modelos de déficit cognitivo e doenças neurodegenerativas em peixe-zebra (Danio rerio) - Bortolotto, Josiane Woutheres (2015)
Alzheimer disease (AD) and Parkinson disease (PD) are the two most common neurodegenerative disorders affecting around 35 and 10 million people worldwide, respectively. These disorders are characterized by neuronal protein deposits and progressive loss of function or structure of central nervous system (CNS). Studies have shown that purinergic system is involved in mechanisms associated with neurodegenerative diseases such as AD and PD. The purinergic signaling is meditated by ATP and adenosine through activation of purinoceptors P2 and P1, respectively. The nucleotide and nucleoside levels are modulated by the action of the ectonucleotidase family, especially by ecto-Nucleoside triphosphate diphosphohydrolases (NTPDases) and ecto-5´-nucleotidase (EC-5´-Nt). These enzymes hydrolyze ATP to adenosine, which is subsequently deaminated by the enzyme Adenosine Deaminase (ADA) to inosine. Adenosine is described as an important neuromodulator and neuroprotective of CNS, and its modulation has proven to be a promising alternative for the treatment of neurodegenerative diseases. Thus, this study aims to evaluate behavioral parameters in models of cognitive impairment induced by scopolamine, 6-hydroxydopamine, and paraquat in zebrafish and study the possible effect of these models on the purinergic system. Our results, using a model of pharmacological cognitive impairment induced by scopolamine in adult zebrafish, showed that selective and non-selective inhibitors of adenosine receptors (Caffeine, ZM241385, and DPCPX) prevented the cognitive deficit induced by scopolamine. The same results were found for the adenosine transporter inhibitor (dipyridamole), and ADA inhibitor (EHNA). These data support the hypothesis of adenosinergic signalling can modulate memory mechanisms. We also developed a new experimental model of neurodegeneration by treating adult zebrafish chronically with paraquat herbicide (Pq) that results in symptoms of PD. Treatment consisted of six ip. injections of Pq in doses of 10 or 20 mg/kg and each injection was administered every three days. Locomotor behavior was assessed 24 hours after each injection and showed a decrease in both doses. The turn angle was also evaluated and showed difference between the doses administered compared to control group. Non-motor behaviors such as anxiety and social interaction were not significantly different after chronic treatment with Pq. However, after Pq exposure, the animals showed a deficit in Y-maze task memory. Apart from the behavioral data, our results presented an increase on dopamine levels, whereas DOPAC decreased in the experimental group showing change in dopamine metabolism. The amount of tyrosine hydroxylase demonstrated no significant difference between control and treated fish; however, dopamine transporter expression decreased in the group treated with 10 mg/kg Pq, and there was no change at the highest dose. Our study also evaluated the effect of chronic exposure of Pq and 6-hydroxydopamine (6-OHDA) neurotoxins, commonly used as an animal model of PD, on extracellular nucleotide and nucleoside metabolism. Two doses of 6-OHDA were tested, 25 and 50 mg/kg, and the animals were sacrificed at six days after exposure. Our data showed no changes in ectonucleotidase activities or ATP, ADP and AMP levels after exposure to Pq. However, a decrease of extracellular adenosine and increase in inosine levels were observed when compared to the control group. The 6-OHDA treatment did not affect the activity of NTPDase, EC-5´-Nt, and ATP levels in both tested doses. In contrast to the previous results, ADP levels were different for each dose used, while the AMP levels decreased in both doses. The adenosine and inosine showed an increase in both doses of 6-OHDA tested in zebrafish brains. These data suggest that the purinergic system can be modulated differently in experimental animals with symptoms of Parkinson's disease. In addition, this study also presented a new model of neurodegeneration using the Pq and confirms the involvement of purinergic system on neurodegeneration as well as its pharmacological potential in neurodegenerative diseases.